Complete mitochondrial genome analysis of Leptomias sp. (Coleoptera, Curculionidae) from Southeast Tibet of China. Issue 3 (2nd July 2020) - Xiang, Dong; Zhuoga, Deqing; Zhen, Wang; Zang, Jiancheng
Abstract: Leptomias sp. belongs to Coleoptera, Curculionidae, Leptomias Faust. It is mainly distributed in the Himalayas and Yarlung Zangbo River valleys in Tibet. It is the first time to report the complete mitochondrial genome of Leptomias sp., which featured a typical circular molecule of 16, 801 bp in length, including 13 PCGs, 22 tRNAs, two rRNAs, and one control region. The overall nucleotide composition was 38.7% of A, 10.0% of G, 34.3% of T, and 17.0% of C. The content of A + T was higher than G + C. In this study, we also determined that Leptomias sp. was the sister to the Sympiezomias velatus based the phylogenetic analysis of nucleotide sequence datasets. This study provides a useful resource for further studies on conservation and population genetics of Leptomias species.